La aplicación de las medidas cautelares a los menores Infractores dentro de un proceso judicial. - Huiracocha Loaiza, Maritza Alejandra (Machala: Universidad Técnica de Machala., 2016)
En el presente caso analizare un caso de un adolescente infractor y debatiremos si este derecho de la medida cautelar con privación de libertad debe ser tramitado En el CAPÍTULO I determinamos lo referente a las generalidades como introducción, problemática, justificación, definición del objeto de estudio, hechos de interés, base jurídica en que se basó el Fiscal y el juez para conceder la remisión y los objetivos del análisis del caso de investigación. En el CAPÍTULO II se trata los fundamentos teóricos-epistemológicos del estudio del caso y las bases teóricas de la investigación para lo cual tuve que recurrir a la lectura y recolección de información de leyes, tratados internacionales y la Constitución de la República.
The study of children in conflict with the law, making a brief reference on their behavior and possible factors which would lead to violating the law, the process that has to cross, attached to internal rules such as the code of childhood and adolescence, Constitution of the Ecuador, and externally different standards international human rights that is based on the principles and guarantees of the right on the issue of young offenders. In this work analyzer the case of a teenage offender and discuss duties precautionary measures are appropriate in this litigation. In Chapter I we determined relation the General characteristics as problematic, justification, introduction, definition of the object of study, events of interest, legal basis on which was based the Prosecutor and the judge to grant remission and the analysis of the case of research objectives. In Chapter II the basics is teoricos - epistemologicos study of the case and the theoretical bases of the research for which I had to resort to reading and collecting information of laws, international treaties and the Constitution of the Republic.
Keywords: ADOLESCENTE; INFRACTOR; REMISION; INFRACCION